Analysis of HR Management and Organizational Support in Maintaining Employee Well-Being and Performance When Working from Home During COVID-19 - Kurniawan, Dediek Tri; Sopiah, .; Juariyah, Lohana; Prohimi, Afwan Hariri Agus; Salleh, Muhammad Syukri (KnE Social Sciences, 2021)
he COVID-19 pandemic has paralyzed the economy in many countries. The Indonesian government decided to implement large-scale social restrictions to handle COVID-19. This policy encouraged various activities to be carried out at home. Some companies decided to encourage their employees to work from home (WFH). This study aimed to explore HR policies during the COVID-19 pandemic in maintaining employee performance in airport-management companies. This research used online questionnaires to reduce face-to-face interaction and was assisted by the HR departments in the companies. This research confirmed that HR practices and perceived organizational support positively influenced job performance. This study could not show the role of employee well-being as a mediator, which is related to HR practices and POS not having been proven to affect employee well-being. In addition, the results did not show that employee well-being affects job performance. Keywords: Maintaining Employee, Organizational Support, Performance, HR Policies, Work From Home